POLITIK DAN PENDIDIKAN (Tinjauan Historis Pengaruh Kebijakan Politik Terhadap Sistem Pendidikan di Indonesia) - Asrori, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Problems of education in Indonesia is the product of political interest of ruler, therefore they use it as a tool of authority. Education as subsystem of the state has function as supplier of educated people, it can succeed in development. In this beloved country, the reality of problems in education can not be separated from the effort to gain the authority. Therefore, educations sector is the medium for the success of the policy to achieve the goal and principal aspiration its leadership